CHALLENGES AND PERSPECTIVES RELATED TO CLIMATE CHANGE AND FOOD SECURITY IN BRAZIL (REMUNOM, 2025)
The article explores the relationship between climate change and food security, emphasizing the challenges confronting the global agricultural sector, with a particular focus on Brazil. Climate change has intensified extreme events such as droughts, floods, and heatwaves, adversely affecting agriculture and quality of life. The research utilized the Science Direct database to analyze peer-reviewed articles related to climate change and food security. Direct impacts of climate change on the productivity of crops such as rice, soybeans, and maize were identified, influenced by factors like temperature, precipitation, and solar radiation. Deforestation and land-use changes also contribute to alterations in rainfall patterns, reducing agricultural productivity. Consequently, forest preservation is highlighted as essential for food security, as it regulates microclimates and hydrological cycles. Policies that promote forest conservation and agricultural adaptation are critical to addressing climate challenges, protecting biodiversity, and ensuring sustainable food production.